Crude enzymatic broth from lipoliptic fungi for the production of metylic esters - Bessa, Dâmaris Hadassa Rangel Fonseca; Flumignan, Danilo Luiz [UNESP]; Souza, Amanda Oliveira; Gonçalves, Mariana Costa Mello; Castro, Carlos Frederico de Souza (Centro Universitario de Maringa, 2022)
Biodiesel, derived from vegetal and animal prime matter, is a renewable fuel that has recently been highlighted as a possible replacement for fossil fuels, especially diesel. Biodiesel is obtained by transesterification or esterification, where lipases which may be synthesized by lipolytic fungi used as catalysts. Current research analyzes the prospection of lipolytic enzymes in fungi and employed crude enzymatic broth to produce biodiesel. The growth of fungi occurred in a mineral medium with a single carbon source: extra-virgin olive oil. Crude broth was analyzed by spectrophotometry using p-NPB as substrate to quantify lipases. Crude broth produced was employed without any modification with different proportions of a central plan composed of soybean and methanol for the production of methyl esters analyzed in gas chromatography. Fungi Paecilomyces formosus (Sakag. & Tada & Samson) I, Paecilomyces formosus II and Aspergillus tubingensis Mos. respectively produced a specific lipolytic activity of 9.268 U g-1, 7.032 U g-1 and 6.447 U g-1. From the crude broth directly used for the production of biodiesel, a rate of 41.60% of methyl esters was obtained. Results show that the fungi´s lipases are active and, when applied directly in the crude broth medium, transesferification is possible with greater rates than those reported in the literature. In fact, the lipase has relevant industrial potential.
Obtenção de caldo bruto enzimático a partir de fungos lipolíticos para a produção de ésteres metílicos
Keywords: Enzymes; Paecilomyces formosus; Renewable energy; Submersed fermentation